Ammonia and methane emissions from dairy concentrated animal feeding operations in California, using mobile optical remote sensing. (15th January 2023) - Vechi, N.T.; Mellqvist, J.; Samuelsson, J.; Offerle, B.; Scheutz, C.
Abstract: Dairy concentrated animal feeding operations (CAFOs) are significant sources of methane (CH4 ) and ammonia (NH3 ) emissions in the San Joaquin Valley, California. Optical techniques, namely, remote sensing by Solar Occultation Flux (SOF) and Mobile extractive FTIR (MeFTIR), were used to measure NH3 air column and ground air concentrations of NH3 and CH4, respectively. Campaigns were performed in May and October 2019 and covered 14 dairies located near Bakersfield and Tulare, California. NH3 and CH4 emission rates from single CAFOs averaged 101.9 ± 40.6 kgNH3 /h and 437.7 ± 202.0 kgCH4 /h, respectively, corresponding to emission factors (EFs) per livestock unit of 9.1 ± 2.7 gNH3 /LU/h and 40.1 ± 17.8 gCH4 /LU/h. The NH3 emissions had a median standard uncertainty of 17% and an expanded uncertainty (95% Confidence Interval (CI)) of 37%; meanwhile, CH4 emissions estimates had greater uncertainty, median of 25% and 53% (in the 95% CI). Decreasing NH3 to CH4 ratios and NH3 EFs from early afternoon (13:00) to early night (19:00) indicated a diurnal emission pattern with lower ammonia emissions during the night. On average, measured NH3 emissions were 28% higher when compared to daytime emission rates reported in the National Emissions Inventory (NEI) and modeled according to diurnal variation. Measured CH4 emissions were 60% higher than the rates reported in the California Air Resources Board (CARB) inventory. However, comparison with airborne measurements showed similar emission rates. This study demonstrates new air measurement methods, which can be used to quantify emissions over large areas with high spatial resolution and in a relatively short time period. These techniques bridge the gap between satellites and individual CAFOs measurements. Highlights: NH3 and CH4 emissions were quantified using direct and indirect flux methods. NH3 and CH4 emission factors averaged 9.1 gNH3 /LU/h and 40.1 gCH4 /LU/h. Day-time NH3 emission factors were 28% higher than estimated by NEI 2014. Quantified CH4 emission factors were 60% higher than the CARB inventory.